2015
DOI: 10.5455/aim.2015.23.29-32
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Applying Podcast Multimedia Teaching System on Motivational Achievement and Learning Among the Boy Students

Abstract: Background:Traditional education classes are no more effective because they are tied to a particular place and time. Podcast complete the defection of other educational resources. In this study we aimed to address whether utilizing podcast multimedia training system has an effect on the motivational achievement and students learning of the Arabic course in high school.Methods:In this practical-purposed, descriptive and quasi-experimental study, pre- and post-test method in control and experiment groups was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…which shown and approved that, students' performances had been effective positively based on used a well-designed practical interactive lesson. For instance, this result agreed with many studies, such as Merkt et al, 2011;Sariscsany & Pettigrew, 1997;Schwan & Riempp, 2004;Zhang et al, 2006;Nozari & Siamian, 2015;Teye, 2011;Nusir et al, 2011), it has been used on lymphoma and leukemia interactive online modules to facilitate the learning for medical students in senior study stage between 2007 and 2009 (Pather et al, 2016). The impact on students' learning was remarkable.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…which shown and approved that, students' performances had been effective positively based on used a well-designed practical interactive lesson. For instance, this result agreed with many studies, such as Merkt et al, 2011;Sariscsany & Pettigrew, 1997;Schwan & Riempp, 2004;Zhang et al, 2006;Nozari & Siamian, 2015;Teye, 2011;Nusir et al, 2011), it has been used on lymphoma and leukemia interactive online modules to facilitate the learning for medical students in senior study stage between 2007 and 2009 (Pather et al, 2016). The impact on students' learning was remarkable.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, by reviewing many of studies over the years, such as Merkt et al, 2011;Sariscsany & Pettigrew, 1997;Schwan & Riempp, 2004;Zhang et al, 2006;Nozari & Siamian, 2015;Teye, 2011;Nusir et al, 2011) have shown that students' performances have been raised and became more enjoyable based on use interactive learning and were more successful than non-interactive students group. According to Najjar "learning was higher when information was presented via computer-based multimedia systems than traditional classroom lectures" (1996, p. 30), interactive learning environment offers to students the opportunities to increase their self-directed and develop their performance (Zhang et al, 2006).…”
Section: Interactive Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee () found that the use of Kakao Talk, a mobile phone‐based app resulted in students who were better prepared and were more motivated in the classroom. Nozari and Siamian () found that utilizing podcast multimedia training system had a positive effect on students and significantly increased learning for students. These technologies may also be incorporated into the CBE and PL curriculum to familiarize students with an array of resources to use for workforce motivation and team‐building.…”
Section: Best Practicesmentioning
confidence: 99%
“…3271 required for natural science (Nozari & Siamian, 2015). Guggenheim and Williams (2015) considered that teachers, in the teaching process, guided students to discuss problems step by step and students found out problems according to facts and collect and verify data to make reasonable explanations, and solve problem for new knowledge.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%